Research on the Application of Computer Intelligent Detection in Civil Engineering Technology. Issue 3 (May 2021) - Zhao, Chunzhi; Yan, Tingsheng; Wang, Guangjun
Abstract: The traditional detection methods of civil engineering are mainly on account of the census detection with typical characteristics of scope, efficiency and cost. These conventional detection methods are mainly on account of voice diagnosis and visual inspection. There is a high demand for the number of samples, otherwise it is difficult to meet the requirements of working accuracy. The iterative maturity of computer intelligent detection technology, its application in the field of civil engineering, greatly promote the improvement of civil engineering detection. On account of this, this paper first analyses the application status of computer intelligent tech in civil engineering, then studies the utilization advantages of computer intelligent detection in civil engineering, and finally gives its specific utilization process.